O espetáculo da vida humana em Cato Maior De Senectute (Nuntius Antiquus, 2010)
The dialogue Cato Maior (De senectute) is often considered the Ciceronian text in which the topos of the “theater of life” (theatrum mundi) is explicitly revealed most frequently (five of the eight times in which it apears in all of the works of this author). Little attention, however, has been given to the effects of this topos on the dialog itself. It has been treated as a mere embellishment (ornatus), e.g. a resource used occasionally to apeal to more popular tastes. However, this article intends, firstly, to show that the theatrum mundi is an integral part of this philosophical dialogue; secondly, to provide a reflection on the theatricalization of the Cato Maior, suggesting philosophical effects arising from the use of the topos.